Managing Services Marketing : Text and Readings - Bateson, John E. G. (Fort Worth The Dryden Press, 1995)
This edition covers topics in services marketing combined with a variety of articles selected from marketing, organisational behavior, operations management, and strategy literature.
Include Illustrations and Index.
Text and Readings.
Keywords: Service industries--Marketing -- Service industries--Management -- Customer services--Management